1994
DOI: 10.1136/ard.53.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of in vivo hprt gene-mutated T cells in the peripheral blood of patients with systemic sclerosis.

Abstract: Objectives-Activated T lymphocytes are involved in the pathogenesis of scleroderma (systemic sclerosis, SSc); such cells rapidly divide in vivo and are thus theoretically subject to random mutation more frequently than resting cells. To study whether SSc is associated with rapidly expanding T cell clones the frequency was determined of in vivo mutated T cells (MF) at the hypoxanthine guanine phosphoribosyl transferase (hprt) gene in the peripheral blood from patients with SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…The observed variance among individual CE estimates under selection or nonselection conditions is also not unusual (13) as it is mainly influenced by the frequency of T cells in the sample. Our results, however, are in contrast to findings for other T-cell-mediated autoimmune diseases such as multiple sclerosis (15,17), type 1 diabetes mellitus (19), rheumatoid arthritis (20), or systemic autoimmune syndromes (17,21,22,24,25), because they do not support a significant difference between the MF values from healthy controls and the patient groups. The reasons for this discrepancy are unclear but the following interpretations are being proposed to …”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The observed variance among individual CE estimates under selection or nonselection conditions is also not unusual (13) as it is mainly influenced by the frequency of T cells in the sample. Our results, however, are in contrast to findings for other T-cell-mediated autoimmune diseases such as multiple sclerosis (15,17), type 1 diabetes mellitus (19), rheumatoid arthritis (20), or systemic autoimmune syndromes (17,21,22,24,25), because they do not support a significant difference between the MF values from healthy controls and the patient groups. The reasons for this discrepancy are unclear but the following interpretations are being proposed to …”
Section: Discussioncontrasting
confidence: 85%
“…Under these premises, the mean frequency of mutant (hprt 2 ) T cells in the HT patient population is expected to be higher than the mean frequency of hprt 2 T cells in healthy subjects, because there should be a stronger proliferative response to thyroid antigens, (i.e., more actively dividing T cells) in the first group. This approach has been analogously used to study the frequency, phenotype, or function of peripheral blood mutant T cells in other autoimmune diseases such as multiple sclerosis (15)(16)(17)(18), type 1 diabetes mellitus (19), rheumatoid arthritis (20), systemic lupus erythematosus (21)(22)(23), mixed connective tissue disease (24), and scleroderma (25).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have now been reported for multiple sclerosis [Allegretta et al, 1990], Guillain-Barre syndrome [Van den Berg et al, 1995], systemic lupus erythematosus Wood et al, 1994;Theocharis et al, 1995], systemic sclerosis [Sfikakis et al, 1994], mixed connective tissue disease [Holyst et al, 1994], rheumatoid arthritis [Cannons et al, 1998], type 1 diabetes mellitus [Falta et al, 1999[Falta et al, , 2000, paroxysmal nocturnal hemoglobinuria [Chen et al, 2004], and malignant melanoma , with results consistent with the basic hypothesis [Albertini, 2001]. On a practical level, it has been found that sudden and dramatic elevations of HPRT MFs in cardiac transplant recipients have been reliable noninvasive indicators of rejection episodes [Ansari et al, 1995].…”
Section: Discussionmentioning
confidence: 98%
“…An elevated frequency of hprt mutant T-cells has been found in several autoimmune diseases, including rheumatoid arthritis [Cannons et al, 1998], multiple sclerosis [Sriram, 1994], systemic lupus erythematosus [Dawisha et al, 1994;Theocharis et al, 1995], scleroderma [Sfikakis et al, 1994], juvenile onset dermatomyositis [Abramson et al, 1999], Guillain-Barré syndrome, and chronic inflammatory demyelinating polyneuropathy [Van den Berg et al, 1995]. The cause of this elevated mutant frequency is unknown, although we earlier postulated that genotoxic RNOS at sites of chronic or recurrent inflammation may be responsible [Cannons et al, 1998].…”
Section: Discussionmentioning
confidence: 99%